The occurrence of the very rare species Gekko cf. brooksii (Squamata, Gekkonidae) in West Sumatra, Indonesia, based on molecular and morphological evidence - MORALITA CHATRI; YUNI AHDA; ZULYUSRI ZULYUSRI; LUHUR SEPTIADI; AWAL RIYANTO; FITRA ARYA DWI NUGRAHA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Chatri M, Ahda Y, Zulyusri, Septiadi L, Riyanto A, Nugraha FAD. 2024. The occurrence of the very rare species Gekko cf. brooksii (Squamata, Gekkonidae) in West Sumatra, Indonesia, based on molecular and morphological evidence. Biodiversitas 25: 3369-3379. Sumatra, Indonesia is a region of vast, rich and diverse flora and fauna, yet knowledge of herpetology in Sumatra is limited. One such group is the genus Gekko, which is poorly known, morphologically diverse and taxonomically problematic, especially for canopy-dwelling geckos. During our recent fieldwork in the Barisan Mountains of West Sumatra, we found an unidentified camouflaged gecko and used molecular and morphological approaches to confirm its identity. Based on molecular (NADH dehydrogenase 2 [ND2] and flanking tRNA genes) and morphological comparisons (31 characters), we confirmed a new record and an expansion range of Gekko cf. brooksii to West Sumatra; we also reported several morphological characters that have not been reported in previous studies. The individual was found on the leaves of a young breadfruit plant (Artocarpus communis J.R.Forst. & G.Forst.) located about 1 meter from the hiking trail, where the surrounding vegetation consisted of several tall trees and was mostly dominated by herbaceous plants that did not exceed 1 meter in height. It conclusion, despite a long history of exploration, the herpetofauna of Sumatra continues to yield new discoveries and records. As the geckos inhabiting the higher canopy layers of tropical rainforests in Sumatra remain largely unknown, further intensive surveys for canopy-dwelling geckos are needed to further elucidate the complete taxonomic composition of Sumatra's herpetofauna.